Microbiological Profile of Chronic Supurative Otitis Media - Shrestha, BL; Amatya, RCM; Shrestha, I; Ghosh, I (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.2 Issue 2 (July-Dec 2011) 6-7 DOI: http://dx.doi.org/10.3126/njenthns.v2i2.6793